2014
DOI: 10.3390/s140610514
|View full text |Cite
|
Sign up to set email alerts
|

Improving Short Term Instability for Quantitative Analyses with Portable Electronic Noses

Abstract: One of the main problems when working with electronic noses is the lack of reproducibility or repeatability of the sensor response, so that, if this problem is not properly considered, electronic noses can be useless, especially for quantitative analyses. On the other hand, irreproducibility is increased with portable and low cost electronic noses where laboratory equipment like gas zero generators cannot be used. In this work, we study the reproducibility of two portable electronic noses, the PEN3 (commercial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 26 publications
1
9
0
Order By: Relevance
“…From the overall percentage result, has shown that the compensation using RT25COMP is able to reduce drift from the original UNCOMP responses with much higher degree than the compensation using T25COMP. This significant drift reduction ability of using RT25COMP from RT-method is congruent with the study in [18], in which utilization of baseline responses in compensating drift would results to a surprising drift-effects reduction. Thus, shows that RT-method is more effective in compensating drift compared to the compensation attempt using T-method.…”
Section: Resultssupporting
confidence: 72%
“…From the overall percentage result, has shown that the compensation using RT25COMP is able to reduce drift from the original UNCOMP responses with much higher degree than the compensation using T25COMP. This significant drift reduction ability of using RT25COMP from RT-method is congruent with the study in [18], in which utilization of baseline responses in compensating drift would results to a surprising drift-effects reduction. Thus, shows that RT-method is more effective in compensating drift compared to the compensation attempt using T-method.…”
Section: Resultssupporting
confidence: 72%
“…This indicated that the device was likely very sensitive to environmental factors and should be trained under the same conditions as testing. Sensor drift due to variation in temperature and humidity may be controlled by periodic calibration with an internal standard based on cotton volatiles [25]. This capability is potentially available with our PAD unit via software correction.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, Macias at al. introduced the basics of an affordable home-made e-nose [38]. Considering the simplicity and the efficiency of this device, parts of the main framework of CAPINose concerning air flows with injections and cleaning steps have been utilized in the AROD's e-nose prototype.…”
Section: Ar Olfactory Device Developmentmentioning
confidence: 99%